Carob (Ceratonia siliqua L.) cultivation, processing, and industrial applications: A review - Lahcen Hssaini; Reda Meziani; Rachid Razouk; Ahmed Irchad (African and Mediterranean Agricultural Journal - Al Awamia)
Carob (Ceratonia siliqua L.), an evergreen tree native to the Mediterranean basin and a member of the Leguminosae family, boasts a rich mosaic of ecological, historical, and economic significance. Beyond its valuable role in the ecosystem and cultural heritage, carob is renowned for its seeds, from which the prized locust bean gum is extracted. This natural thickening and stabilizing agent has garnered substantial attention for its versatile applications across diverse industries, particularly in the food and pharmaceutical sectors. This review delves into the botanical characteristics of carob, highlighting its significance as a source of locust bean gum and exploring its potential industrial applications. Recent advancements and challenges in the extraction and utilization of locust bean gum are critically examined, emphasizing its contribution to sustainable practices within modern industrial processes. The review further investigates the multifaceted role of carob beyond gum production, including its nutritional value, potential in animal feed, and emerging applications in biofuel production. Through this comprehensive analysis, the review aims to illuminate the pivotal role of carob and its derivatives in driving innovation and sustainability across the global market landscape. Carob's unique properties and diverse applications position it as a valuable resource with the potential to address contemporary challenges in food security, sustainable production, and environmental consciousness.